#FlattenTheCurve. (14th September 2020) - Dixon, Robert
Abstract: In this paper I adapt a common model used in economics to study the diffusion of innovations to model the transmission of a virus. Emphasis is placed on the evolution of the number of new infections and the cumulative total number of infections over time and how they might be influenced by different policies. Although the model is very simple it does yield some useful implications for public policy .